PENGARUH NILAI AKTIVA DAN KEWAJIBAN TERHADAP NILAI AKTIVA BERSIH (NAB) REKSADANA SYARIAH DI INDONESIA PERIODE 2019-2023 - Junita Carolina PA (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
The goal of this research is to ascertain if there is a correlation between the value of Islamic mutual funds' liabilities and their net asset value (NAV), as well as the relationship between the two. All Islamic mutual funds registered with the OJK between 2019 and 2023 comprise the population of this study. The quantitative methodology of the research uses secondary data sources. To get a sample of ten Islamic mutual fund businesses, the sampling procedure was then conducted using purposeful sampling. They next analyze the gathered data using IBM SPSS Statistics 30. data analysis that uses multiple linear regression analysis to assess the hypothesis. According to a research on the topic, the NAB of Islamic mutual funds in Indonesia is significantly influenced by the value of both assets and liabilities. Along with asset value, obligations have a significant impact on Indonesia's Islamic mutual fund NAB. Keywords: Sharia Mutual Funds, Asset Value, Liabilities, Net Asset Value (NAV)